2011
DOI: 10.1039/b913880n
|View full text |Cite
|
Sign up to set email alerts
|

Visible light photoredox catalysis: applications in organic synthesis

Abstract: The use of visible light sensitization as a means to initiate organic reactions is attractive due to the lack of visible light absorbance by organic compounds, reducing side reactions often associated with photochemical reactions conducted with high energy UV light. This tutorial review provides a historical overview of visible light photoredox catalysis in organic synthesis along with recent examples which underscore its vast potential to initiate organic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
1,263
0
27

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,661 publications
(1,341 citation statements)
references
References 66 publications
9
1,263
0
27
Order By: Relevance
“…Initial investigations into the photoredox activation of TCTs was performed using an iridium complex ( fac ‐[Ir(ppy) 3 ], Ir (III) ),[[qv: 9a]] which has been extensively employed for a variety of organic transformations 23. With appropriate stoichiometry, Boyer and co‐workers demonstrated that these systems were able to furnish well‐defined polymers under irradiation from a blue LED ( λ max = 435 and 460 nm) for a variety of different monomers (both activated and less activated monomers).…”
Section: Tct Activation Via Photoredox Catalysismentioning
confidence: 99%
“…Initial investigations into the photoredox activation of TCTs was performed using an iridium complex ( fac ‐[Ir(ppy) 3 ], Ir (III) ),[[qv: 9a]] which has been extensively employed for a variety of organic transformations 23. With appropriate stoichiometry, Boyer and co‐workers demonstrated that these systems were able to furnish well‐defined polymers under irradiation from a blue LED ( λ max = 435 and 460 nm) for a variety of different monomers (both activated and less activated monomers).…”
Section: Tct Activation Via Photoredox Catalysismentioning
confidence: 99%
“…In the last three decades, photocatalytic processes promoted by semiconductors (SC) have found a widespread application in many fields, including water splitting, energy production, air and water purification, surface sterilization and organic synthesis (17)(18)(19)(20)(21)(22)(23). The reasons for this increasing interest in photocatalytic protocols are the growing demand for reducing environmental pollution and for developing more eco-friendly and cheaper processes.…”
Section: Photocatalytic Activity In Semiconductorsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Ru-and Ir-based coordination complexes have received enormous attention because of their excellent visible-light-harvesting properties, modest to extremely high oxidation and reduction potentials, relatively long excited-state lifetimes, and reasonably good chemical and photostabilities under synthetic oxidative and reductive conditions. [2] In addition, considerable efforts have been made to develop metal-free photoredox catalytic methods with organic dyes [8,[10][11][12][13][14] such as eosin Y [10,11] or rhodamine derivatives [13,14] and organic heterogeneous photocatalysts [15] for synthetic transformations.…”
Section: Introductionmentioning
confidence: 99%